PROFIL FUNGSI KOGNITIF PASIEN PASCA STROKE DI RAWAT JALAN RSUD AJI MUHAMMAD PARIKESIT TENGGARONG - Nova, Dewa Made Rama; Hutahaean, Yetty Octavia; Irawiraman, Hadi (Jurnal Medika : Karya Ilmiah Kesehatan, 2023)
Stroke is the second mortality and highest disability cause in the world. One of its complications is cognitive impairment. This study aims to determine the cognitive function profile, cognitive impairment domain’s distribution, and profile based on gender, age, educational level, occupational history before stroke, and the pathology types in post-stroke patients at the outpatient department of RSUD Aji Muhammad Parikesit Tenggarong. This study used descriptive observational design with a cross-sectional approach. The primary data were obtained through interviews using MoCA-Ina and the secondary data from the medical records. There were 92 samples of post-stroke patients were collected with the consecutive sampling method. The results showed that 94.6% of the respondent suffered from cognitive impairments. Almost all of the cognitive domains were impaired, the worst of all was delayed recall (98.8%). Mostly male (47.8%), respondents aged 55-64 years old (39,1%) suffered high school level (32.6%), and 42.4% economically inactive, ischemic stroke (91.3%) respondents suffered from cognitive impairment. This research concludes that primarily post-stroke patients suffered from cognitive impairment where delayed recall was the most affected domain and cognitive impairment occur most in male, aged 55-64 years old, enrolled in high School, inactive economically, and with ischemic stroke had cognitive impairment.